A Study on the perceptions of the University of the Philippines-Diliman students and head librarians on coffee shops in the UPD libraries - Manuel, Melyssa Lauren M.; Arlante, Salvacion M. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2011)
Many libraries abroad have installed coffee shops or coffee carts in their libraries for the convenience of their patrons and to attract more users. This research, entitled "A Study of the Perceptions of University of the Philippines - Diliman Students and Head Librarians On Coffee Shops in the UPD Libraries," aims to determine the probable effectiveness of adapting this concept in the local setting. In particular, it focused on collecting and differentiating data on the perceptions of chosen University of the Philippines Diliman students and head librarians about coffee shops and coffee vending machines inside or in the vicinity of the UPD libraries. The chosen libraries were the College of Law Library, the Main Library, the College of Mass Communication Library, and the College of Engineering Libraries. A total of 200 students - 50 students from each library - answered the survey, and five head librarians were interviewed.
The data gathered from the survey of 200 students showed that (1) the respondents consume an average of 7 cups of coffee every week, 3 of which are consumed outside their homes; (2) they occasionally read or study while drinking coffee; (3) they visit a UPD Library at an average of two times every week, each visit lasting 40 to 60 minutes; (4) they have positive perceptions about coffee shops in or near the vicinity of the library; and (5) they prefer a coffee shop over a coffee vending machine, and that it be a popular and already known commercial coffeehouse.
Further analysis of the survey results showed several differences, i. e. : (1) the respondents who prefer coffee shops have more positive perceptions than those who prefer coffee vending machines and those who are undecided between the two concessions; (2) respondents who often read or study while drinking coffee have more positive perceptions than those who rarely and never read or study while drinking coffee; (3) respondents from the Main Library are more inclined toward outsourcing from popular coffeehouses than the respondents from the College of Mass Communication, the College of Law and the College of Engineering; (4) Outsourcing from popular coffeehouses is also preferred by the respondents who visit the library twice a week and those who visit every day; and (5) respondents who claim to visit the library almost never, once and three times a week are uncertain or undecided if they prefer popular coffeehouses or unpopular coffeehouses.
Ms. Ramos of the Main Library, Atty. Santos of the Law Library, Ms. Lapuz of the Social Sciences and Philosophy Library, Ms. Santos of the Mass Communication Library, and Ms. Esposo of the Engineering Libraries were interviewee and they all have positive perceptions about having a coffee shop or vending machine as an additional service in the library.
The researcher recommends that further data be gathered on whether students prefer the coffee shop or coffee vending machine to be installed inside the library walls or simply adjacent or near the library. Further study on what other products, besides coffee, are preferred by the library users is also recommended. This would help library management predict the menu.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Coffee shops -- Philippines -- Quezon City; University of the Philippines(Diliman) -- Students; Librarians; University of the Philippines(Diliman) -- Libraries